2021
DOI: 10.1002/dad2.12158
|View full text |Cite
|
Sign up to set email alerts
|

Odor identification impairment and cholinesterase inhibitor treatment in Alzheimer's disease

Abstract: Introduction:This study evaluated acute change in odor identification following atropine nasal spray challenge, and 8-week change in odor identification ability, as a predictor of long-term improvement in patients with mild to moderate Alzheimer's disease (AD) who received open-label cholinesterase inhibitor treatment. Methods:In patients with clinical AD, the University of Pennsylvania Smell identification Test (UPSIT) was administered before and after an anticholinergic atropine nasal spray challenge. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In preclinical AD, patients can experience subjective cognitive decline that causes them concern, although classic neuropsychological tests are not able to detect any change in cognition at this time …”
Section: Pathophysiologymentioning
confidence: 99%
“…In preclinical AD, patients can experience subjective cognitive decline that causes them concern, although classic neuropsychological tests are not able to detect any change in cognition at this time …”
Section: Pathophysiologymentioning
confidence: 99%
“…However, results regarding the impact of AChEIs on olfactory function in patients with AD are inconsistent. Some studies have found that olfactory function is improved by treatment with AChEIs (34,35) and have even suggested that atropine challenge is indicative of a cognitive response to AChEI treatment; however, further studies did not confirm these findings (36,37). It is important to note that odor identification was tested in these studies, and olfactory memory was not specifically analyzed.…”
Section: Discussionmentioning
confidence: 87%
“…However, change in UPSIT after atropine challenge was not associated with AChEI benefit, contrarily to the previously cited study. The authors hypothesized that this lack of association was due to the fact that atropine, administered through nasal spray, might have not reached the olfactory bulb, but the small sample may have also contributed to this negative finding (Motter et al, 2021 ). Although it did not include patients with neurodegenerative dementias, a small RCT by Pelton suggested that a lower UPSIT score could predict cognitive response to donepezil at 3 months in depressed patients with cognitive impairment, reinforcing the hypothesis that AChEI therapy would be generally beneficial in patients with hallmarks of cholinergic deficit, irrespective of the diagnosis (Pelton et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%